Prophylactic use of the Angel® catheter in a patient with paraneoplastic syndrome scheduled for surgical tumor resection. A case report and literature review - Stamenković, Dušica M.; Nešković, Vojislava; Marjanović, Ivan; Tomić, Aleksandar; Rusović, Siniša; Marinković, Vlastimir; Bančević, Vladimir; Karanikolas, Menelaos (Vojnosanitetski pregled, 2021)
Introductio. The Angel® catheter (BiO2 Medical Inc, San Antonio, Texas, USA) is a novel device that combines a triple lumen central venous catheter with an inferior vena cava filter for prevention of pulmonary embolism (IVC filter-catheter). Case report. We present the case of a 53- year-old male patient with renal carcinoma and a history of recent deep venous thrombosis (DVT) on oral anticoagulation who was scheduled to undergo open radical nephrectomy. Because of concerns about the risks from documented pre-existing DVT, we decided to insert the Angel® catheter preoperatively in order to have central venous access during surgery and also to reduce the risk of perioperative pulmonary embolism. On the first postoperative day, active gastric bleeding was detected and nadroparine was stopped. Before removal of the Angel® catheter, a pre-removal cavagram revealed large thrombus mass in the catheter filter. Because of the presence of the thrombus mass, the catheter was removed surgically, after a permanent vena cava filter was inserted. Conclusion. This case suggests that the use of the Angel® IVC filter/3-lumen central catheter combination could be a reasonable option for pulmonary embolism prophylaxis in the patients at a high risk for DVT, such as the patients with malignant disease, paraneoplastic syndrome and chemotherapy who need to undergo surgery.